ANALYSIS OF THE INFLUENCE OF SELF-EFFICACY, PERCEIVED EASE TO USE, PERCEIVED BENEFITS, AND PERCEIVED RISK, ON INTENTION TO USE DIGITAL PAYMENT APPLICATIONS IN YOGYAKARTA - Baliawan, Prastara Rangga Dito; Putranti, Latifah; Herdiany, Hapsari Dyah (Universitas Muria Kudus, 2024)
The flow of technological developments in recent decades has experienced rapid progress and has triggered the emergence of many innovations in various fields, one of which is in the financial sector. A form of innovation in the financial sector is starting to change the way of paying digitally, using digital payment applications. This development was not immediately accepted by society. Based on this problem, this research aims to determine the intention to use digital payment applications in Yogyakarta using the Technology Acceptance Model (TAM) theory, namely self-efficacy, perceived ease of use, perceived benefits, perceived risk. This research used quantitative methods, with 115 respondents from various levels of society in the city of Yogyakarta with a minimum age of 18 years. The data collection method in this research used a questionnaire, and the results obtained were tested using the Structural Equation Model via Smart PLS 4 software by testing 6 hypotheses. The research results show that self-efficacy has a positive influence on the perception of ease of use of digital payment applications in. Self-efficacy has a positive influence on perceived benefits. Self-efficacy has a positive influence on risk perception. Perceived ease of use has a positive influence on Intention to Use. Perceived usefulness has a positive influence on Intention to Use. Risk perception has a positive influence on Intention to Use.